Professional reflection in library activity: theoretical and methodological analysis - L. S. Moskovchuk (Библиосфера, 2012)
The transformation of «The Ethics Сode of Russian Librarians» is analyzed, its functions and significance for forming the image of a professional are identified, and vectors of professional reflection in librarianship are shown.